1992
DOI: 10.1177/00220345920710070101
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Orthodontic Retention on the Mechanical Properties of the Periodontal Ligament in the Rat Maxillary First Molar

Abstract: The load-deformation curves obtained by extraction of the rat maxillary first molar from its socket in the dissected jaw were analyzed so that the effect of orthodontic retention on the mechanical properties of the periodontal ligament could be examined. An elastic band was inserted between the rat maxillary first and second molars for four days, and then the interdental space was filled with resin for four or eight days. The average interdental spaces between the teeth ranged from 315 to 398 μm during the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…It has been shown that restoration of the mechanical strength of the PDL occurs in accordance with the closure of the interdental space after removal of the orthodontic force. 33 …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that restoration of the mechanical strength of the PDL occurs in accordance with the closure of the interdental space after removal of the orthodontic force. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted in an attempt to determine the optimal duration of periodontal stabilization. [13][14][15] An histological approach cannot be applied to patients directly, and a radiological approach can be considered strongly subjective in nature; neither is helpful in assessing the stabilization of the periodontal ligament. Tooth mobility, however, can be used on a longitudinal basis as an indicator of biological changes within the periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth movement was estimated by subtracting the mean of the repeated measured values from the untreated and treated sides (Figure 1b) as described by Hong et al 28 The error of the method based on double measurements performed on 20 randomly selected animals was estimated by using Dahlberg's equation (S ϭ , where n ϭ num-2 ͙⌺ d /2n ber of paired measurements and d ϭ deviations between the two measurements 29 ). The error in measurement was 0.02 mm and was thus considered to be of no further importance.…”
Section: Methodsmentioning
confidence: 99%